Recurrence of Thrombotic Thrombocytopenic Purpura after mRNA-1273 COVID-19 Vaccine Administered Shortly after COVID-19 - Karabulut, Korin; Andronikashvili, Ana; Kapici, Ahmet Hakki (Case Reports in Hematology, 2021)
Thrombotic thrombocytopenic purpura (TTP) is a potentially life-threatening consumptive coagulopathy requiring emergent diagnosis and timely treatment. It is characterized by microangiopathic hemolytic anemia and thrombocytopenia with the development of microthrombi caused by inherited or acquired deficiency of the von Willebrand factor-cleaving protease ADAMTS13 and resulting end-organ damage. Most of the cases are the result of acquired deficiency of ADAMTS13, for which the exact etiology is unknown but reported to be related to various autoimmune disorders, infections, and medications. Our case report features of a patient with a history of idiopathic thrombocytopenic purpura and thrombotic thrombocytopenic purpura, who developed a recurrence of TTP 5 days after his first dose of the mRNA Coronavirus disease 2019 (COVID-19) vaccine (mRNA-1273 vaccine) in the setting of recent COVID-19. The close temporal association between vaccine administration, recent COVID-19, and relapse of remitted TTP raises concern for an enhanced immune reaction to COVID-19 vaccine in the setting of recent COVID-19 and underlying autoimmune disease. The association is not absolute, but given the novelty of COVID-19 and the mRNA COVID-19 vaccine and the relapse timing, it leads us to pose this hypothesis. Vaccine distribution to a larger and more diverse population will allow for an increased rate of adverse event reporting. This case report exemplifies potential safety issues that may be encountered with new vaccine administration in patients with recent COVID-19 and underlying autoimmune disease. There are no specific recommendations for COVID-19 vaccine administration in such patients.